Synthesising evidence regarding hospital to home transitions supported by volunteers of third sector organisations: a scoping review protocol. Issue 7 (5th July 2021) - Nelson, Michelle LA; Armas, Alana; Thombs, Rachel; Singh, Hardeep; Fulton, Joseph; Cunningham, Heather V; Munce, Sarah; Hitzig, Sander; Bettger, Janet Prvu
Abstract : Introduction: Given the risks inherent in care transitions, it is imperative that patients discharged from hospital to home receive the integrated care services necessary to ensure a successful transition. Despite efforts by the healthcare sector to develop health system solutions to improve transitions, problems persist. Research on transitional support has predominantly focused on services delivered by healthcare professionals; the evidence for services provided by lay navigators or volunteers in this context has not been synthesised. This scoping review will map the available literature on the engagement of volunteers within third sector organisations supporting adults in the transition from hospital to home. Methods and analysis: Using the well-established scoping review methodology outlined by the Joanna Briggs Institute, a five-stage review is outlined: (1) determining the research question, (2) search strategy, (3) inclusion criteria, (4) data extraction and (5) analysis and presentation of the results. The search strategy will be applied to 10 databases reflecting empirical and grey literature. A two-stage screening process will be used to determine eligibility of articles. To be included in the review, articles must describe a community-based programme delivered by a third sector organisation that engages volunteers in the provisions of services that support adults transitioning from hospital to home. All articles will be independently assessed for eligibility, and data from eligible articles will be extracted and charted using a standardised form. Extracted data will be analysed using narrative and descriptive analyses. Ethics and dissemination: Ethics approval is not required for this scoping review. Members of an international special interest group focused on the voluntary sector will be consulted to provide insight and feedback on study findings, help with dissemination of the results and engage in the development of future research proposals. Dissemination activities will include peer-reviewed publications and academic presentations.